The effect of pH and collector dosage on the flotation performance of arsenopyrite and pyrite - Avelar, Erica; Evans, Cathy; Dunne, Rob; Runge, Kym; Manlapig, Emmy (SAIMM, 2021)
Flotation reagent schemes applied to both greenfield projects and brownfields gold operations are derived from extensive bench scale testwork programs targeted at maximising the recovery of gold and gold-bearing minerals at an acceptable grade for downstream processing. The reagent schemes developed are specific to the ores tested and can vary greatly. A literature review shows xanthate dosages from 5 to 600 g/t have been applied as collectors for bulk flotation of gold-bearing sulfide minerals at a pH range from 3 to 11. Research shows pH influences the formation of dixanthogen and pyrite oxidation, consequently affecting the contacting angle and pyrite hydrophobicity, likewise increasing xanthate dosage promotes pyrite hydrophobicity by changing the contact angle resulting in increased pyrite recovery. This research involves performing experiments according to a Central Composite Rotatable Design using a synthetic pyrite and arsenopyrite ore system to identify flotation kinetic changes based on the xanthate dosage and pH of the slurry.